2021
DOI: 10.33380/2305-2066-2021-10-4(1)-179-187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neuroprotective activity of a new allylmorpholine derivative in a rat model of traumatic brain injury

Abstract: Introduction. The search for and development of new drugs capable of reducing the severity of neurological deficit in traumatic brain injury are a critical task for investigational pharmacology. Chromone-containing allylmorpholines are a new group of neuroprotective drug candidates that have been shown to inhibit acetylcholinesterase and butyrylcholinesterase, and block N-methyl-D-aspartate receptors in vitro.Aim. This study aimed to evaluate the neuroprotective activity of the allylmorpholine derivative (E)-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Compound 5 has been previously evaluated as a potential neuroprotecting agent in rats with unilateral traumatic brain injury; however, it failed to demonstrate any neuroprotective activity. Nonetheless, it induced dose-dependent sedation in rats [ 18 ] and in zebrafish in our experiment. Notably, the CCAMs exerted a sedative effect over a wide range of concentrations; this could be related not only to their different inherent activities shown in vitro [ 13 ] but also to their varying solubility in water, which would affect their availability and the exposure of zebrafish to them.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Compound 5 has been previously evaluated as a potential neuroprotecting agent in rats with unilateral traumatic brain injury; however, it failed to demonstrate any neuroprotective activity. Nonetheless, it induced dose-dependent sedation in rats [ 18 ] and in zebrafish in our experiment. Notably, the CCAMs exerted a sedative effect over a wide range of concentrations; this could be related not only to their different inherent activities shown in vitro [ 13 ] but also to their varying solubility in water, which would affect their availability and the exposure of zebrafish to them.…”
Section: Discussionmentioning
confidence: 60%
“…As both AChE and NMDAR have long been considered viable therapeutic targets for neuroprotection and cognitive enhancement [ 14 , 15 , 16 , 17 ], CCAMs appear to be a promising group of drug candidates for the treatment of neurological disorders. In a recent study, a novel CCAM was found to exert sedation in rats with traumatic brain injury [ 18 ]. However, to the best of our knowledge, no in vivo screening of this class of compounds’ behavioral activity has been performed to date.…”
Section: Introductionmentioning
confidence: 99%